Solvent-based Fabrication Method for Magnetic, Shape-Memory Nanocomposite Foams. (2020) - Luetzow, Karola; Weigel, Thomas; Lendlein, Andreas
ABSTRACT: This paper presents shape-memory foams that can be temporarily fixed in their compressed state and be expanded on demand. Highly porous, nanocomposite foams were prepared from a solution of polyetherurethane with suspended nanoparticles (mean aggregate size 90 nm) which have an iron(III) oxide core with a silica shell. The polymer solution with suspended nanoparticles was cooled down to -20 °C in a two-stage process, which was followed by freeze-drying. The average pore size increases with decreasing concentration of nanoparticles from 158 µm to 230 µm while the foam porosity remained constant. After fixation of a temporary form of the nanocomposite foams, shape recovery can be triggered either by heat or by exposure to an alternating magnetic field. Compressed foams showed a recovery rate of up to 76 ± 4% in a thermochamber at 80 °C, and a slightly lower recovery rate of up to 65 ± 4% in a magnetic field.